Perceived stress among undergraduate medical students and its association with learning strategies and academic performance in Medical College Kolkata, India - Poulomi Mukherjee; Mousumi Datta (Future of Medical Education Journal, 2023)
Background: Stress is an inevitable and important part of being a medical student. Present study explores perceived stress among undergraduate medical students and the correlation of stress with learning strategies and academic performance.Method: This descriptive cross-sectional study was carried out at Medical College Kolkata, India. The target population was undergraduate medical students from phase II and III. Participants’ learning strategies was measured using the modified Approaches to Learning Medicine (mALM) questionnaire. The stress level of the students was determined by Perceived stress Scale (PSS 10). Academic performance was measured in terms of percentages scored in the last MBBS examination. Data were analysed using SPSS version 21. Frequencies and percentages were calculated for categorical variables and measures of central tendency and dispersion was calculated for continuous variables. Differences of mean were tested by independent samples t-test. Correlation was tested by Pearson correlation test.Results: There were 136 students enrolled in the study; and 129 (94.8%) students scored above 60% in their last MBBS examination. Mean PSS score of the participants was 19.4± 4.17. One hundred and twenty-three (90.4%) students were found to have moderate stress. Deep learning approach was significantly more for MBBS Phase III students (p=0.003). However, perceived stress had no significant correlation with either learning strategy (p=0.916) or academic performance of students (p=0.309).Conclusion: Perceived stress was found to be high among undergraduate medical students in the present study. However, any particular learning style or academic performance was not found to be associated with stress.